2013
DOI: 10.1007/s00429-013-0535-5
|View full text |Cite
|
Sign up to set email alerts
|

Linking novelty seeking and harm avoidance personality traits to basal ganglia: volumetry and mean diffusivity

Abstract: Novelty Seeking (NS) and Harm Avoidance (HA) temperamental traits are related to approaching or avoiding motivational circuits relying on the integrity and functionality of distributed brain areas implicated in arousal and action. The present study verified whether and how macro- and micro-structural variations of basal ganglia are correlated with scores obtained in the NS and HA temperamental scales of the Temperament and Character Inventory by Cloninger. To this aim, 125 healthy adults aged 18-67 years of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 79 publications
2
26
1
Order By: Relevance
“…More elaborate structural changes, such as dendritic sprouting, neurogenesis, and angiogenesis, occur over a period of days to weeks. Given the rapid plasticity of MD, it may be related to individual cognitive states and not just individual traits, as shown previously (Laricchiuta et al 2013).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…More elaborate structural changes, such as dendritic sprouting, neurogenesis, and angiogenesis, occur over a period of days to weeks. Given the rapid plasticity of MD, it may be related to individual cognitive states and not just individual traits, as shown previously (Laricchiuta et al 2013).…”
Section: Introductionmentioning
confidence: 72%
“…Previously, neurological studies have shown that patients with Parkinson's disease exhibited a greater MDDS (Péran et al 2010). Studies of normal samples have shown that the major personalities are associated with MD in overlapping areas of the dopaminergic system (Laricchiuta et al 2013;Takeuchi et al 2015). However, it was not clear which factor contributed to MDDS in previous studies, because different personalities were associated with MD in similar areas.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It can sensitively detect the neural plasticity involving dopamine function change (Razek et al, 2011;Takeuchi et al, 2014c). It also shows robust correlation with the motivational state, which is highly relevant to dopamine as well as traits crucially related to dopamine (Bjørnebekk et al, 2012;Laricchiuta et al, 2013;Picerni et al, 2013;Takeuchi and Kawashima, 2013). Thus, DRD polymorphism may well be associated with these DTI measures, and its investigation can reveal new insights into the effects of DRD4 polymorphisms.…”
Section: Introductionmentioning
confidence: 99%